(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
In this work, the effect of electric permittivity and thin layer thickness on the energy gape has been studied in a system consisting of three thin layers by means of finding the self action potential of charge carrier located in the central layer of this system. Then, the self action potential energy has been found by solving Schrödinger equation at the extracted potential. This study shows that energy gape of PbI2 decreases with layer thickness while it increases/decreases according to comparison between dielectric permittivity values of central layer and counterparts of two neighborhood layers on both sides, respectively.